Group policy : fundamentals, security, and the managed desktop - Moskowitz, Jeremy (Serious skills., 2013)
The Ultimate Book on Group Policy Freshly updated to include Windows 8 and Windows Server 2012, Group Policy: Fundamentals, Security, and the Managed Desktop, Second Edition is the book for learning everything you need to know about Group Policy, no matter which version of Windows you use. Microsoft Group Policy MVP Jeremy Moskowitz covers it all-major Group Policy categories, what Windows 8 and Windows Server 2012 bring to the table, and smart ways to tackle tough desktop management problems.